EXPOSED AND ENDANGERED: DOXXING AS A GENDERED HUMAN RIGHTS VIOLATION AGAINST WOMEN IN THE GLOBAL CONTEXT - Mari A. Dewees (PEOPLE: International Journal of Social Sciences, 2026)
Doxxing, the non-consensual public release of women's private identifying information, has emerged globally as a systematic instrument of gendered digital violence. It is used to silence, threaten, and punish women for public visibility and civic participation. This study examines doxxing as a structurally gendered human rights violation, analyzing its global prevalence, consequences, and the adequacy of legal and institutional responses across national and international governance contexts. Using qualitative document analysis, the research draws on publicly available sources including UN Special Rapporteur reports, CEDAW committee documentation, civil society publications from organizations such as Amnesty International and PEN America, national legislative texts from multiple jurisdictions, and peer-reviewed scholarship. Findings reveal that women worldwide face coordinated doxxing campaigns with severe consequences including physical endangerment, psychological trauma, and the silencing of professional and civic participation. Legal frameworks across most jurisdictions are fragmented and ill-equipped to address doxxing's cross-border, gendered dimensions, and international human rights instruments, while normatively instructive, remain non-binding and inconsistently enforced. The study concludes that doxxing against women constitutes a serious and under-addressed human rights crisis demanding doxxing-specific legislation, binding international standards, and enforceable platform accountability mechanisms that center the safety and dignity of women in the digital public sphere.